The species of Colletinae (Hymenoptera: Colletidae) in the Brazilian state of Minas Gerais - Ferrari, Rafael R.; Silveira, Fernando A. (Zootaxa, 2015)
The Brazilian state of Minas Gerais is a species-rich territory about as large as France, which houses the headwaters of some of the most important rivers in Brazil, as well as a variety of phytogeographic domains, with a poorly known insect fauna. Here, a synopsis of the bee species included in the genera Colletes Latreille, 1802 and Rhynchocolletes Moure, 1943 (Colletidae: Colletinae) occurring in this state is presented, including synonymies, diagnoses, redescriptions and identification keys to females and males of the eight recognized species, including one described as new. These species are Rhynchocolletes albicinctus Moure, 1943; Colletes altimontanus Ferrari & Silveira sp. nov.; C. argentinus Friese, 1908 stat. rev., C. meridionalis Schrottky, 1902; C. ornatus Schrottky, 1902; C. petropolitanus Dalla Torre, 1896; C. rufipes Smith, 1879; and C. rugicollis Friese, 1900. Colletes extensicornis Vachal, 1909 is here proposed to be a junior synonym of C. meridionalis.